Uvulitis as a New Sign of COVID-19 - SeyedAlinaghi, SeyedAhmad; Attarian, Niloofar; Tabari, Amir; Mehraeen, Esmaeil; Jahanfar, Shayesteh (Coronaviruses, 2026)
COVID-19 is the disease, caused by the virus accountable for the latest global pandemic, has caused millions of mortalities and morbidities since its initial spread in 2019, originating in Wuhan, China. The virus is thought to have originated from an animal coronavirus before acquiring the capability of human-to-human transmission and causes acute respiratory syndrome. The virus also presents as a multi-systemic disorder with diverse manifestations across various bodily systems. Over time, we have observed both short-term and long-term complications arising from it. Oral manifestations, particularly uvulitis, have been less studied compared to other symptoms of COVID-19. There is a need for further research to enhance our knowledge about rare symptoms.
Keywords: Respiratory syndrome